Cooperative Localization and Object Recognition in Autonomous UWB Sensor Networks - Zetik, Rudolf; Yan, Honghui; Malz, Elke; Jovanoska, Snezhana; Shen, Guowei; Thomä, Reiner S.; Salman, Rahmi; Schultze, Thorsten; Tobera, Robert; Willms, Hans-Ingolf; Reichardt, Lars; Janson, Malgorzata; et al. (IntechOpen, 2013)
None